Probing solvent accessibility of amyloid fibrils by solution NMR spectroscopy - Ippel, Johannes H. (National Academy of Sciences, 2002)
Amyloid is the result of an anomalous protein and peptide aggregation, leading to the formation of insoluble fibril deposits. At present, 18 human diseases have been associated with amyloid deposits—e.g., Alzheimer's disease and Prion-transmissible Spongiform Encephalopathies. The molecular structure of amyloid is to a large extent unknown, because of lack of high-resolution structural information within the amyloid state. However, from other experimental data it has been established that amyloid fibrils predominantly consist of β-strands arranged perpendicular to the fibril axis. Identification of residues involved in these secondary structural elements is therefore of vital importance to rationally designing appropriate inhibitors. We have designed a hydrogen/deuterium exchange NMR experiment that can be applied on mature amyloid to enable identification of the residues located inside the fibril core. Using a highly amyloidogenic peptide, corresponding to residues 25–35 within the Alzheimer Aβ(1–43) peptide, we could establish that residues 28–35 constitute the amyloid core, with residues 31 and 32 being the most protected. In addition, quantitative values for the solvent accessibility for each involved residue could be obtained. Based on our data, two models of peptide assembly are proposed. The method provides a general way to identify the core of amyloid structures and thereby pinpoint areas suitable for design of inhibitors.